COMPARISON OF BILIARY STENTING AND SURGICAL BYPASS IN PALLIATIVE MANAGEMENT OF IRRESECTABLE PERIAMPULLARY CARCINOMA - Shah, Syed Fahad; Hameed, Sania; Aurakzai, Jehanzeb Khan; Raza, Ali; Chaudhry, Muhammad Amjad; Shah, Syed Hussain; Shah, Syed Zubair (Journal of Ayub Medical College Abbottabad, 2018)
Background: Some 20-40% of the periampullary carcinoma is irresectable at the time of diagnosis. Biliary stenting and surgical bypass are commonly used palliative procedure. There is no consensus favouring one procedure over the other. This study compares the both procedures. Methods: This Randomized Controlled Trial included 47 patients who presented with diagnosis of obstructive jaundice due to periampullary carcinoma to the Department of Surgery, Federal General Hospital, Islamabad from July 2012 to December 2014. Results: Out of total 47 patients 27 (57.44%) were males and 20 (42.55%) were females. Group-A included 25 (53.19%) patients while group-B included 22 (46.81%) patients. The mean age in both groups was 62.34 years (SD=±5.01). All patients died during the study. The mean survival time for the stent patients was 7.5 months while the mean survival time for surgical bypass patients was 8.3 months. The jaundice was relived in all surgical (22, 100%) of the patients as compared to (18, 72%) of the patients in stent group. Conclusion: We concluded that surgical bypass as a primary procedure in selected patients provided better jaundice relieve as compared to biliary stenting. Keywords: Periampullary Carcinoma; Biliary Stent; Malignant Jaundice